Taxmann's Right to Information law and practice with case book on Right to Information / by R.K.Verma and Anuradha Verma - Verma, R.K (New Delhi, 2010)
Disclosure of Government Information in India is governed by a law enacted during the British rule over large parts of what is now India, the Official Secrets Act of 1889 which was amended in 1923. This law secures information related to security of the State, sovereignty of the country and friendly relations with foreign states, and contains provisions which prohibit disclosure of non-classified information. Civil Service conduct rules and the Indian Evidence Act impose further restrictions on government officials' powers to disclose information to the public
Keywords: Right to Information law